Innovative Ecosystem: a Model of Innovative Development of the Russian Regions - V. Lyulyuchenko, Mikhail; I. Seliverstov, Yurii (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the present paper is to consider modern problematic situations in the field of innovative development of the Russian Federation and its regions, as well as to study the tools to eliminate the revealed problems. In the course of the research, a problem of a non-uniform innovative development of RF regions has been revealed. Solution to the situation can be concentration of efforts on the developed regions or formation of favorable conditions for the innovative development in all regions for the efficient operation of the national innovative system. In this case, a rational tool is the process of formation of the innovative ecosystem of the region, which is characterized by an optimal interrelation between the participants of the innovation process based on the principles of self-organization and self-control. On the basis of the research conducted, the unified model of the innovative ecosystem of the region has been formed, and the adaptation whereof to the conditions of a certain region will allow increasing its innovative activity.